2011
DOI: 10.3389/fnsys.2011.00021
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Stereotypic Responses of Basal Ganglia Neurons to Subthalamic Nucleus High-Frequency Stimulation in the Parkinsonian Primate

Abstract: Deep brain stimulation (DBS) in the subthalamic nucleus (STN) is a well-established therapy for patients with severe Parkinson's disease (PD); however, its mechanism of action is still unclear. In this study we explored static and dynamic activation patterns in the basal ganglia (BG) during high-frequency macro-stimulation of the STN. Extracellular multi-electrode recordings were performed in primates rendered parkinsonian using 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine. Recordings were preformed simultaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
72
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 60 publications
15
72
0
Order By: Relevance
“…In contrast, beta oscillations and synchrony were reduced dramatically. Similar observations have been made by others during high-frequency microstimulation of the GPi (Bar-Gad et al 2004;Erez et al 2009;Chiken and Nambu 2013) or the STN (Meissner et al 2005;Moran et al 2011).…”
supporting
confidence: 74%
“…In contrast, beta oscillations and synchrony were reduced dramatically. Similar observations have been made by others during high-frequency microstimulation of the GPi (Bar-Gad et al 2004;Erez et al 2009;Chiken and Nambu 2013) or the STN (Meissner et al 2005;Moran et al 2011).…”
supporting
confidence: 74%
“…There is persistent ambiguity regarding the effect of STN DBS on neuronal firing rates in nuclei downstream of the STN (GPe and SNr/GPi), and previous human and animal studies reported both decreases (Benazzouz et al 2000;Beurrier et al 2001;Magariños-Ascone 2002;Moran et al 2011;Welter et al 2004) and increases (Hahn et al 2008;Hashimoto et al 2003;Maurice et al 2003;Reese et al 2011) in firing rates during STN DBS. Our results show that regardless of the regularity of the stimulation pattern, highfrequency STN DBS generated both decreases and increases in firing rates, and changes in the mean firing rate did not correlate with behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report a spectrum of firing rate changes in response to DBS resulting in no net change in the mean firing rate in rats (Bosch et al 2011;Chang et al 2006;McConnell et al 2012;Shi et al 2006), nonhuman primates Moran et al 2011), and humans (Reese et al 2011). This mixture of excitatory and inhibitory responses in GPe and SNr neurons during STN DBS differed during behaviorally effective high-frequency DBS compared with ineffective low-frequency DBS (McConnell et al 2012), suggesting that the mixture of firing rate responses may contribute to the mechanism of DBS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all the importance placed on mechanisms, the mechanisms by which DBS affects the signs of MDs are still unknown despite decades of research using animals [239][240][241]. This is an important element in our analysis of animal models and DBS as one of the reasons animal models in general have been heralded as important, indeed vital, is for the search for mechanisms.…”
Section: Epistemology and Mechanismsmentioning
confidence: 99%